Natural Carbon Isotope Composition Distinguishes Compound Groups of Biogenic Volatile Organic Compounds (BVOC) in Two Mediterranean Woody Species - Haberstroh, Simon; Kreuzwieser, Jürgen; Boeddeker, Helena; Eiblmeier, Monika; Gutte, Helene; Lobo-do-Vale, Raquel; Caldeira, Maria C.; Werner, Christiane (Frontiers in Forests and Global Change, 2019)
Our knowledge on the biosynthesis of several biogenic volatile organic compounds (BVOCs) is still limited. In this regard, natural abundant stable carbon isotope ratios (δ13C) of BVOCs may provide a powerful tool to evaluate different metabolic pathways. In the present study, BVOC emissions and their carbon isotope composition from two Mediterranean species, Quercus suber L. and Cistus ladanifer L. were investigated under field conditions in June and July 2018. Soil water content decreased between these months, which was reflected by an increase of the photosynthetic discrimination from -27.7 ± 0.2‰ to -26.2 ± 0.2‰ in Q. suber and from -27.0 ± 0.3‰ to -26.1 ± 0.3‰ in C. ladanifer. This change made an impact on the signatures of various BVOCs, which varied along a very broad range of -28.0‰ to -42.6‰ in June and -23.7‰ to -32.9‰ in July. Hence, the increasing photosynthetic discrimination had a cascading effect on the natural carbon isotope composition of the emitted BVOCs over time. Consistent differences in compound classes occurred among species and seasons: acyclic monoterpenoids were the most 13C enriched compound class (-23.7 – -31.3‰), followed by slightly more depleted cyclic monoterpenes (-27.6 – -32.9‰) and sesquiterpenes (-26.4 – -32.1‰). The detected oxygenated cyclic monoterpenoids (-31.5 – -37.0‰) and benzenoid aromatic compounds (-30.6 – -42.6‰) were strongly 13C depleted. Hierarchical clustering based on δ13C values confirmed the grouping of BVOCs with similar chemical structures to the same cluster. Hence, we suggest that isotopic fractionation occurs during the cyclization and oxygenation processes of monoterpenoids, as well as during the synthesis of volatile benzenoid aromatic compounds. The differences in δ13C values between BVOCs were consistent, although we collected BVOCs under highly varying light conditions, air temperatures, emission rates and from two different species. Here, we demonstrate that the natural carbon isotope composition may provide a robust framework to elucidate biosynthetic pathways of various BVOCs under field conditions.